The species specificity of the microimmunofluorescence antibody test and comparisons with a time resolved fluoroscopic immunoassay for measuring IgG antibodies against Chlamydia pneumoniae. Issue 2 (1st February 1999) - Wong, Y K; Sueur, J M; Fall, C H; Orfila, J; Ward, M E
Abstract : AIMS: To examine the species specificity of the microimmunofluorescence test (MIF) and assess a time resolved fluoroscopic immunoassay (TRIA) for measuring IgG antibodies to C pneumoniae. METHODS: Sera from 1020 subjects were tested by MIF for IgG, IgM, and IgA antibodies to C pneumoniae, C trachomatis, and C psittaci; 501 serum samples were also tested by TRIA for IgG antibodies to C pneumoniae. RESULTS: C pneumoniae antibody titres as measured by MIF were correlated with those for C psittaci and trachomatis. It was estimated that on average, one third of the twofold dilution steps that make up the final C pneumoniae antibody titre may be due to cross reacting genus specific antibody. The results of TRIA correlated well with those of MIF. In 75% of cases, the TRIA result predicted a three titre range within which the actual MIF result would fall. CONCLUSIONS: MIF does not appear to be as species specific as claimed. TRIA is unlikely to be as specific but as it is completely objective, easier to perform, amenable to automation, and gives reproducible results, it is a rapid and useful method for comparing populations.